Screening Instruments to Detect the Risk of Early Weaning in Infants: A Literature Review - Oktafiana, Defa; Rosyidah, Hanifatur; Aisyaroh, Noveri (Jurnal EduHealth, 2025)
There was a decrease in the percentage of exclusive breastfeeding in 2019 at 67.74%, a decrease from 68.74% in the previous year, showing a statistical decrease of 1.0%. In an effort to increase exclusive breastfeeding and prevent premature weaning, it is important to have measuring tools or instruments that can identify women at risk based on planned behavior theory. This Literature Review aims to find out the instruments that can be used to detect the risk of early weaning in babies. The method used is a systematic literature review by conducting a search through several databases, namely PubMed and Google Scholar. The search period is limited to the last 10 years, namely between 2013 to 2023 and 10 articles were obtained in this study. The BSES-SF instrument was used to measure confidence in breastfeeding. BAPT is used to predict the early cessation of breastfeeding by considering various factors, while BBAT provides an assessment of efficient breastfeeding techniques. Finally, the LATCH Score helps in evaluating breastfeeding practices and can predict the risk of stopping breastfeeding early. All of these instruments have an important role in supporting successful breastfeeding practices, both in research and in clinical practice.